The biogenic amine and mineral contents of different milling fractions of bread and durum wheat (Triticum L.) cultivars. (October 2020) - Karayigit, Belgizar; Colak, Nesrin; Ozogul, Fatih; Gundogdu, Ali; Inceer, Huseyin; Bilgiçli, Nermin; Ayaz, Faik Ahmet
Abstract: Comparative analysis of biogenic amines (BA) and mineral element contents in various bread and durum wheat ( Triticum L.) cultivars from different milling fractions (whole flour, bran, white flour and semolina) were studied. Concentrations of 5 BA (putrescine, spermidine, spermine, agmatine and serotonin) and 10 elements (Ca, Mg, Na, K, P, Zn, Cu, Al, Mn, and Fe) in the milling fractions were analysed using high-performance liquid chromatography (HPLC) and inductively coupled plasma mass spectrometry, respectively. The bran milling fraction showed the highest agmatine content in all cultivars, which also had considerable amounts of spermidine (range: 34–40 mg/100 g dw), followed by whole and white wheat flours, and semolina. The major mineral in bran was P followed by K and Mg. In general, the bread wheat cultivars showed higher mineral contents than the durum wheat cultivars, while on the other hand, BA content in bread wheat cultivars was generally lower than in durum wheat cultivars. The variation in BA and minerals content in the wheat cultivars can be used in wheat breeding programs to improve the nutritional quality of wheat grains. The milling fraction was more important in the distribution of BA and minerals in grains than the cultivar. The contents and the differences in the milling fractions are also important when foods or feeds are being formulated.